2020
DOI: 10.3390/ijns6020047
|View full text |Cite
|
Sign up to set email alerts
|

It All Depends What You Count—The Importance of Definitions in Evaluation of CF Screening Performance

Abstract: Screening metrics are essential to both quality assessment and improvement, but are highly dependent on the way positive tests and cases are counted. In cystic fibrosis (CF) screening, key factors include how mild cases of late-presenting CF and CF screen positive, inconclusive diagnosis (CFSPID) are counted, whether those at prior increased risk of CF are excluded from the screened population, and which aspects of the screening pathway are considered. This paper draws on the New Zealand experience of almost f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…NBS reporting protocols are expected to result in clear and concise information exchange. A recent report in NZ emphasized that, to enable meaningful comparisons, CF screening reports should include the screening algorithm and target along with clarification of the steps in the screening pathway included in the assessment, the screening algorithm, and screening target [ 608 ]. To encourage faster recall returns for follow-up testing overall, a structured protocol for follow-up of inadequate and borderline positive NBS (including text messages to specimen submitters) was recently introduced [ 609 ].…”
Section: Resultsmentioning
confidence: 99%
“…NBS reporting protocols are expected to result in clear and concise information exchange. A recent report in NZ emphasized that, to enable meaningful comparisons, CF screening reports should include the screening algorithm and target along with clarification of the steps in the screening pathway included in the assessment, the screening algorithm, and screening target [ 608 ]. To encourage faster recall returns for follow-up testing overall, a structured protocol for follow-up of inadequate and borderline positive NBS (including text messages to specimen submitters) was recently introduced [ 609 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, these centres of expertise should be selected and supervised by medical specialty societies in accordance with objectively defined quality criteria [ 140 , 142 ]. At the programme level, clear case definitions and guidelines for confirmation diagnostics are required for all target diseases [ 1 , 31 , 32 , 33 , 81 , 94 , 143 , 144 , 145 , 146 ].…”
Section: Resultsmentioning
confidence: 99%
“…Standardised algorithms for confirmatory diagnostics, as well as case definitions for all target diseases, are crucial for the consistent reporting of NBS programmes, monitoring outcomes in newborns with confirmed diagnoses, and evaluating the NBS benefit [ 32 , 33 , 81 , 94 , 143 , 144 , 145 ]. Good epidemiological practices include defining all variables of interest precisely and operationalising them in a standardised way [ 162 ].…”
Section: Resultsmentioning
confidence: 99%
“…To accurately compare different screening approaches, outcome data need to be collected consistently and accurately. It has been shown that different definitions of parameters significantly impact the calculation of global screening metrics such as specificity, PPV and sensitivity [21] . Metrics are dependent on the way tests and cases are counted unless definitions are clearly harmonized and they are the cornerstone for both quality assessment and improvement of programmes.…”
Section: Discussionmentioning
confidence: 99%